The Sacred in the Landscape of the City - Hodor Katarzyna; Fekete Albert (Technical Transactions, 2019)
In current times of progressing desacralisation, a retrospective view of the transformations that take place in building this phenomenon from the landscape perspective of the city appears essential. The work’s main objective is the identification of the ongoing process on two scales: the micro and macro-scale and over time. The initial outline of the subject is meant to present the phenomenon within the structures of the city, the manner of its shaping and influence on the surroundings, orientation within space and strength of impact.